2015
DOI: 10.1016/j.drugalcdep.2015.04.020
|View full text |Cite
|
Sign up to set email alerts
|

The interest in eight new psychoactive substances before and after scheduling

Abstract: a b s t r a c tBackground: In recent years the recreational use of new psychoactive substances (NPS) has increased. NPS are considered a threat to public health and the main response to this threat is to make the selling and buying of these substances illegal. In Sweden, during the last 5 years, 62 new substances have been classified as narcotics but little is known of the effects of making a particular substance illegal. The aim of this work is to study how legal status influences the interest in NPS in Swede… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 23 publications
(31 reference statements)
0
25
0
Order By: Relevance
“…In Sweden, each new harmful substance is regulated individually, following identification and risk assessment evaluation . Once the regulation is enforced, the substance is generally taken off the domestic open web‐based NPS market (Internet drugs) and replaced by other structural variants with similar pharmacological action, so that sales will continue to be legal (legal highs) . Over the last ~8 years, several hundred new substances intended as recreational drugs or as legal alternatives to the classical, controlled illicit drugs have been introduced…”
Section: Discussionmentioning
confidence: 99%
“…In Sweden, each new harmful substance is regulated individually, following identification and risk assessment evaluation . Once the regulation is enforced, the substance is generally taken off the domestic open web‐based NPS market (Internet drugs) and replaced by other structural variants with similar pharmacological action, so that sales will continue to be legal (legal highs) . Over the last ~8 years, several hundred new substances intended as recreational drugs or as legal alternatives to the classical, controlled illicit drugs have been introduced…”
Section: Discussionmentioning
confidence: 99%
“…Consumers' interest changed and most possibly turned towards even more emerging NPSs, such as MDPV or pentedrone. Most recently, Ledberg () presented similar results, as he found that the activity on an internet discussion forum related to NPSs was significantly decreased around the time of classification.…”
Section: Discussionmentioning
confidence: 68%
“…NPS that are not controlled under drug laws are desirable to both the suppliers and users, such as experimentation and production without fear of incarceration (Brandt, Sumnall, Measham, & Cole, ). Once a substance is controlled by international and/or national drug laws, one study found that interest in that drug declines (Ledberg, ). Research has found that displacement of drugs from one supplier to another, for example, from high‐street retailer to street‐level drug dealer, is reflective of its legal status (Sumnall, Evans‐Brown, & McVeigh, ).…”
Section: Introductionmentioning
confidence: 99%